Clinical trial: Effects of treatment with a vibrating capsule in patients with severe chronic constipation - Lembo, Anthony; Simons, Madison; Loesch, Jack; Hamza, Eyad; Graff, Erica Loren; Quigley, Eamonn; Rao, Satish S. C. (Alimentary pharmacology & therapeutics, 2024)
Summary Background There is little information on the effectiveness of therapies for severe chronic constipation. In a phase 3 trial, we previously demonstrated that a vibrating capsule was significantly more efficacious than a placebo in chronic constipation. Aim To examine the effects of a vibrating capsule and placebo on symptoms and health‐related quality of life (HRQoL) in patients with severe chronic constipation. Methods We performed a post hoc analysis of phase 3, multicentre, randomised, double‐blind, and placebo‐controlled 8‐week clinical trial of a vibrating capsule to specifically assess outcomes among subjects who reported 0 complete spontaneous bowel movements (CSBMs) during the 2‐week baseline period. We assessed effects of treatment on bowel symptoms, patient satisfaction, and HRQoL. CSBM responders were defined as subjects with increases of ≥1 or ≥2 or ≥3 weekly CSBMs (CSBM1 or CSBM2, CSBM3, respectively) over baseline for ≥6 out of 8 weeks of treatment. Results The severe chronic constipation subgroup comprised 175 (56%) of the 312 subjects. Significantly more subjects with severe chronic constipation who received the vibrating capsule than those who received the placebo were CSBM1 (44.9% vs. 20.9%, p = 0.007), CSBM2 (29.2% vs. 11.6%, p = 0.004), and CSBM3 (19.10% vs 6.98%, p = 0.017) responders. Straining effort, stool consistency, patient satisfaction, and HRQoL significantly improved in the severe chronic constipation subgroup. A mild vibrating sensation was reported in 10%. Conclusion The vibrating capsule significantly improved constipation‐related symptoms and HRQoL in patients with severe constipation, affirming its efficacy and safety across the spectrum of chronic constipation. Post hoc analysis was performed in participants with severe chronic idiopathic constipation (CIC), defined as 0 complete spontaneous bowel movements (CSBM) during the 2 week baseline period of the phase 3 trial with a vibrating capsule. The severe CIC group comprised 175 (56%) of the 312. Significantly more participants with severe CIC who received VC compared to those who received placebo had an increase of at least 1, 2, or 3 weekly CSBMs (i.e. CSBM1, CSBM2, and CSBM3, respectively).